Analyses of Ice Core Data from Various Sites in Svalbard Glaciers from 1987 to 1999 - Motoyama, Hideaki; Watanabe, Okitsugu; Fujii, Yoshiyuki; Kamiyama, Kokichi; Igarashi, Makoto; Matoba, Sumito; Kameda, Takao; Goto-Azuma, Kumiko; Izumi, Kaoru; Narita, Hideki; Iizuka, Yoshinori; Isaksson, Elisabeth (National Institute of Polar Research, 2008)
P(論文) Dataset : Analyses of Ice Core Data from Various Sites in Svalbard Glaciers from 1987 to 1999 | https://ads.nipr.ac.jp/dataset/A20130131-011 departmental bulletin paper